A Comparison of Plyometric and Jump Rope Training Programs for Improving Punching Performance in Junior Amateur Boxers - Chottidao, Monchai; Kuo, Chia-Hua; Tsai, Shiow-Chwen; Hwang, Ing-Shiou; Lin, Jiu-Jenq; Tsai, Yung-Shen (Frontiers in Bioengineering and Biotechnology, 2022)
Improving lower extremity sports performance may contribute to punching performance in boxers. We compared the effects of two typical boxing routines for developing lower extremity sports performance and subsequent punching performance. Twenty-four high school amateur boxers between the ages of 12 and 18 performed training at least 3 days per week. All Athletes had 3–5 years of experience in boxing training. The participants separated into two groups to receive an 8-week plyometric or jump rope training program. They performed each training program for 30 min on 3 days/week. Lower extremity sports performance in countermovement jump (leg stiffness, jump power, and rate of force development) and jab-cross punching performance (punch velocity, punch force, reaction time, movement time, and ground reaction force) were assessed at pre-and post-training. The data were analyzed using a two-way mixed-design analysis of variance (ANOVA) (group × time). Both training programs improved the rate of force development in countermovement jump, the reaction time of punch, the peak ground reaction force of the rear leg during the jab punch, and the velocity of the jab punch. There were no group differences and interaction effects in all variables analyzed. It is concluded that 8 weeks of plyometric and rope jumping programs had a similar impact on improving lower extremity strength and punching performance. Both training programs may improve muscle strength and power, rate of force development, and reaction time. These improvements may contribute to lower extremity strength for driving a punch at the target with excellent performance.